Nitrogen loss in internal-loop granular sludge bed nitrifying reactor - LU Gang; ZHENG Ping; HU Bao-lan; JIN Ren-cun (浙江大学学报. 农业与生命科学版)
The nitrogen loss in internal-loop granular sludge bed nitrifying reactor was studied, and the results indicated that ammonia escape is an important factor causing nitrogen loss. Based on double film theory and thermodynamics theory, the kinetic model for ammonia escape was constructed, and factors affecting the ammonia escape were investigated. The model predictions for ammonia escape were in good agreement with the experimental data and therefore could be used to predict the nitrogen loss in the reactor. The sensitivity analysis showed that pH is the most sensitive parameter affecting ammonia escape.